The process of forming students’ pedagogical professionalism: A case study at Hanoi National University of Education in Vietnam - Khanh, Mai Quoc; Tinh, Tran Trung; Giang, Trinh Thuy; Hong, Nguyen Thi Thanh; Kien, Phan Trung; Quang, Nguyen Vinh (Linguistics and Culture Review, 2021)
Objectives of the study: Assessing the process of students’ forming pedagogical professionalism at Hanoi National University of Education (HNUE), Vietnam. Research Methods: We used the polling method through questionnaires to collect information for the research process. Two questionnaires were designed for two groups of subjects, group 1 for 203 students and group 2 for 18 administrators and lecturers. We use mathematical statistical methods, and data analysis to make judgments. Research results: A part of students do not have a full sense of pedagogical professionalism. The process of forming students’ pedagogical professionalism has not been clearly shaped from the identification and implementation of goals, principles, content and activities involved in this process. At the end of the study, we propose four measures to overcome the above limitations at HNUE.